Sigla (Sigla_II_IV) - Robinson, James M. (BrillOnline Reference Works, 2012)
A subscript dot placed under a letter indicates that the letter is visually uncertain, even if the context seems to make the reading certain. Visual certainty does not depend upon the amount of surviving ink but upon the exclusion of all other alternatives than the one presented in the transcription. Dots on the line indicate the number of missing letters of which ink vestiges survive when letters are not restored